The Role of Work Engagement in Mediating the Influence of 360 Degree Leadership and Digital Literacy on Team Effectiveness in FJB Jakarta Construction Company - Faiz Rabbani Fasy; Rifat Indrawan Laya; Tinjung Desy Nursanti (Universitas Mercu Buana, 2023)
This study aims to find out the role of Work Engagement in mediating the influence of 360-Degree Leadership and Digital Literacy on the Team Effectiveness of construction services company FJB in Jakarta. The research method used in this study is a quantitative-associative method. The data was collected by distributing a five-point Likert scale questionnaire to FJB construction service employees as a cross-sectional sample. Questionnaire data was then recapitulated and processed using a path analysis approach that included descriptive and verification analysis. Path analysis is used to calculate the effect of 360-degree leadership and digital literacy on team effectiveness through work engagement. Total respondents who became the sample in this study were 113 respondents. The results of the path analysis show that the 360-degree leadership variable is also the digital literacy variable, both directly and indirectly, having a positive effect on work engagement, and the work engagement variable also has a positive and significant effect on the team effectiveness variable. The influence of the 360-degree leadership and digital literacy variables on team effectiveness through work engagement also shows positive and significant results.